2020
DOI: 10.1097/bot.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Publication Rates of Posters From the Orthopaedic Trauma Association Annual Meeting 2011–2016: Posters Are Not Second Rate

Abstract: Objective: To determine the publication rate of posters presented at the OTA annual meeting from 2011 to 2016. Methods: All posters presented at the OTA annual meetings from 2011 to 2016 were identified from the OTA's official website and confirmed through review of the OTA official programs. This information was then used to direct a search, and if the presentation was associated with a publication, publishing information was entered into the database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Several studies of academic conferences in other surgical subspecialties revealed publication rates of 31.1% at the British Association of Head and Neck Oncologists annual meeting, 69.9% at the American Academy of Orthopaedic Surgeons annual meeting and 54% at the Orthopaedic Trauma Association annual meeting. 16–18 The studies from other national subspecialty organizations are in line with our findings for the AUA Annual Meeting. Additionally, the publication rate for RCTs in our study was 65.6%, which is comparable to past analysis of RCT publication.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Several studies of academic conferences in other surgical subspecialties revealed publication rates of 31.1% at the British Association of Head and Neck Oncologists annual meeting, 69.9% at the American Academy of Orthopaedic Surgeons annual meeting and 54% at the Orthopaedic Trauma Association annual meeting. 16–18 The studies from other national subspecialty organizations are in line with our findings for the AUA Annual Meeting. Additionally, the publication rate for RCTs in our study was 65.6%, which is comparable to past analysis of RCT publication.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding that many abstracts were published in advance of presentation is a common finding among academic conferences, and this trend has been observed in the past at the AUA Annual Meeting. 6,16,18 The time to publication, while similar to past AUA Annual Meeting studies, is much shorter than recent studies in other surgical subspecialties: 19.4 months at the Orthopaedic Trauma Association annual meeting and 18.8 months at the British Association of Head and Neck Oncologists annual meeting. 6,16,18 This may suggest that AUA Annual Meeting abstracts that achieve publication may be closer to a final product than at other academic conferences.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…is trend towards higher publication rates in recent years is reflected throughout orthopedics. Publication rates for national orthopedic meetings ranged from 34% to 67% in the 1990s, compared to 54% to 74% in recent reports, which is similar to our results [1][2][3][8][9][10][11][12][13][14][15][16]. e OTA meeting is one wellstudied example, with relatively high publication rates overall that increased from 67% (1994 to 1998) to 73% (2008 to 2012) for podium presentations [2,3].…”
Section: Sarcomasupporting
confidence: 88%